2014
DOI: 10.1590/0004-282x20140096
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment of small-for-gestational age infants: behavioral aspects in first year

Abstract: The purpose of this study was to compare the behavior of full-term small-for-gestational age (SGA) with full-term appropriate-for gestational age (AGA) infants in the first year of life. We prospectively evaluated 68 infants in the 2 nd month, 67 in the 6 th month and 69 in the 12 th month. The Bayley Scales of Infant Development-II were used, with emphasis on the Behavior Rating Scale (BRS). The groups were similar concerning the item "interest in test materials and stimuli"; there was a trend toward differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
4
0
3
Order By: Relevance
“…In total, 89 samples from 60 studies including 52 822 children compared preterm and term-born children who had IUGR and were SGA with children with AGA with respect to cognitive outcomes. A total of 48 studies reported results for mean cognitive scores, and 24 studies reported the percentages of group-specific children with BII …”
Section: Resultsmentioning
confidence: 99%
“…In total, 89 samples from 60 studies including 52 822 children compared preterm and term-born children who had IUGR and were SGA with children with AGA with respect to cognitive outcomes. A total of 48 studies reported results for mean cognitive scores, and 24 studies reported the percentages of group-specific children with BII …”
Section: Resultsmentioning
confidence: 99%
“…There are many research trials confirming the impact of SGA on neurodevelopmental delay in children born on time (23,24). In recent years, studies have concentrated on evaluating the possibility of SGA being an independent risk factor for developmental impairment in premature children.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous epidemiologic studies have suggested broad associations between small size at term birth and risk of suboptimal or damaged neurodevelopment. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Most are small or include only single outcomes, such as cognition, behavior, school performance, and general neurodevelopment at various ages. There are fewer studies of risk among term births for specific neurodevelopmental outcomes.…”
Section: Figure 2 Ors Of Various Neurodevelopmental Conditionsmentioning
confidence: 99%